1994
DOI: 10.1007/bf00843456
|View full text |Cite
|
Sign up to set email alerts
|

Direct endoscopic percutaneous jejunostomy (EPJ)

Abstract: Direct puncture of the small bowel under endoscopic guidance (direct EPJ) is possible in patients whose stomach has been removed or whose small bowel cannot be punctured by other methods. From January 1990 to June 1992 a total of 39 patients underwent successful direct EPJ at our institution. The indications were malnutrition after partial or total gastrectomy (n = 19), insufficient anastomosis or a stenosis after esophageal resection and esophagojejunostomy (n = 13), esophageal perforation (n = 3), fistulas (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 10 publications
2
16
0
8
Order By: Relevance
“…D-EPJ can normally placed without problems in patients with partial or post-gastrectomy and is considerably more diffi cult prior to surgery [52][53][54] .…”
Section: Percutaneous Tube Feedingmentioning
confidence: 99%
“…D-EPJ can normally placed without problems in patients with partial or post-gastrectomy and is considerably more diffi cult prior to surgery [52][53][54] .…”
Section: Percutaneous Tube Feedingmentioning
confidence: 99%
“…Several series examining the safety of surgical jejunostomy and DPEJ have reported favorable results with few complications [4,[6][7][8][9]. Myers [7].…”
Section: Discussionmentioning
confidence: 96%
“…During the mean follow-up of 107 days, none of the patients with DPEJ required reintervention for tube malfunction or displacement. Mellert et al reported their experience with DPEJ in 44 patients over a 2-year period [9]. The predominant indication was malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…For a Mayo clinic series, the success rate of direct percutaneous jejunostomy tube insertion was 73% [18]. The insertion of the PEJ carries a success rate of 64 to 92.3% [17,[19][20][21][22]. For ultrasound/fluoroscopically guided PEJ placement, the success rate is 87% [23].…”
Section: Discussionmentioning
confidence: 98%